Why, o God?: suffering and disability in the Bible and the church - Waters, Larry J. (Crossway, 2011)
Redeeming suffering / Joni Eareckson Tada -- A biblical disability-ministry perspective / Daniel R. Thomson -- Church-based disability ministries / Jessica James Baldridge -- Disabilities and the church / Michael A. Justice -- The rolling throne / Gregory A. Hatteberg -- Suffering in the Pentateuch / Stephen J. Bramer -- Suffering in the historical books / Stephen J. Bramer -- Suffering in the book of Job / Larry J. Waters -- Suffering in the Psalms and Wisdom Books / Ronald B. Allen -- Suffering in the writing prophets (Isaiah to Malachi) / Stephen J. Bramer -- A biblical theology of suffering in the Gospels / Mark L. Bailey -- Suffering in Acts and the Pauline Epistles / Stanley D. Toussaint -- Suffering in the Non-Pauline Epistles / james E. Allman -- Suffering in the Book of Revelation / Thomas L. Constable -- Receiving evil from God / Douglas K. Blount -- Pastoral care and disability / Victor D. Anderson -- Global suffering / James A. Neathery -- Dealing with disabilities in adults / Amy J. Wilson -- Children with disabilities / Patricia Evans -- Bioethics and suffering / Richard L. Voet -- Death and dying / Linda M. Marten -- Wheelchairs in heaven? / Joni Eareckson Tada